Clinical pattern of antibiotic-associated syndrome in children receiving different antibacterial therapy - L.B. Golden; A.A. Ploskireva; E.V. Kanner; I.D. Kanner (LCC «Medicine-Inform», 2021)
L.B. Golden1, A.A. Ploskireva2,3, E.V. Kanner2, I.D. Kanner4 1Infectious Clinical Hospital No. 2, Moscow, Russian Federation 2Central Research Institute of Epidemiology of the Russian Federal Service for Supervision of Consumer Rights Protection and Human Well-Being, Moscow, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4Lomonosov Moscow State University, Moscow, Russian Federation Aim: to describe the clinical pattern of antibiotic-associated diarrhea (AAD) and extraintestinal manifestations of antibiotic-associated syndrome (AAS) in children receiving different antibacterial therapy. Patients and Methods: this prospective clinical observational study was conducted in 2017-2019. The study included 231 children aged three months to 13 years admitted for community-acquired pneumonia and received antibacterial treatment. Clinical presentations of AAS (diarrhea, vomiting, dyspepsia, stomatitis) and extraintestinal presentations of AAS were evaluated in all children within a month after antibacterial treatment. In addition, clinical presentations of AAS were compared in children who received β-lactam antibiotics or macrolides. Results: AAS symptoms were diagnosed in 64.5% of children, while diarrhea was observed in 25%. In patients who received β-lactam antibiotics, the most common gastrointestinal (GI) signs were diarrhea, dyspepsia, loss of appetite, and constipation. In children who received ampicillin, the rate of GI signs was lower. In total, GI signs in AAS were less common in children who received macrolides compared to children who received β-lactam antibiotics. Minimal symptoms were associated with clarithromycin. Conclusion: AAS is one of the clinical manifestations of adverse effects of antibacterials on the human organism, including AAD and extraintestinal symptoms. The highest safety profile characterizes clarithromycin in terms of AAS. Keywords: antibiotic-associated diarrhea, antibiotic-associated syndrome, adverse drug reactions, antibacterial treatment, macrolides, adverse effects, antibiotic-associated colitis. For citation: Golden L.B., Ploskireva A.A., Kanner E.V., Kanner I.D. Clinical pattern of antibiotic-associated syndrome in children receiving different antibacterial therapy. Russian Journal of Woman and Child Health. 2021;4(3):260-267 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-260-267.